Find the best solutions to your questions at Westonci.ca, the premier Q&A platform with a community of knowledgeable experts. Explore in-depth answers to your questions from a knowledgeable community of experts across different fields. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.
Sagot :
To evaluate the limit [tex]\(\lim_{x \to \pi / 2} \frac{\sin^2 x + 5 \sin x - 6}{\sin x - 1}\)[/tex], we can proceed as follows:
1. Substitute [tex]\(\sin x\)[/tex] with a new variable:
Let [tex]\( y = \sin x \)[/tex]. As [tex]\( x \)[/tex] approaches [tex]\( \pi/2 \)[/tex], [tex]\( \sin x \)[/tex] approaches 1. Therefore, we will analyze how the function behaves as [tex]\( y \)[/tex] approaches 1.
The limit then becomes:
[tex]\[ \lim_{y \to 1} \frac{y^2 + 5y - 6}{y - 1} \][/tex]
2. Simplify the numerator:
Factor the quadratic expression in the numerator [tex]\( y^2 + 5y - 6 \)[/tex]:
[tex]\[ y^2 + 5y - 6 = (y + 6)(y - 1) \][/tex]
This allows us to rewrite the limit as:
[tex]\[ \lim_{y \to 1} \frac{(y + 6)(y - 1)}{y - 1} \][/tex]
3. Cancel the common factor:
Notice that [tex]\( y - 1 \)[/tex] appears in both the numerator and the denominator, so we can cancel it out:
[tex]\[ \lim_{y \to 1} \frac{(y + 6)\cancel{(y - 1)}}{\cancel{(y - 1)}} = \lim_{y \to 1} (y + 6) \][/tex]
4. Evaluate the limit:
As [tex]\( y \)[/tex] approaches 1, we simply substitute [tex]\( y \)[/tex] with 1 in the remaining expression:
[tex]\[ (y + 6) \bigg|_{y = 1} = 1 + 6 = 7 \][/tex]
Therefore, the value of the limit is:
[tex]\[ \lim_{x \to \pi/2} \frac{\sin^2 x + 5 \sin x - 6}{\sin x - 1} = 7 \][/tex]
1. Substitute [tex]\(\sin x\)[/tex] with a new variable:
Let [tex]\( y = \sin x \)[/tex]. As [tex]\( x \)[/tex] approaches [tex]\( \pi/2 \)[/tex], [tex]\( \sin x \)[/tex] approaches 1. Therefore, we will analyze how the function behaves as [tex]\( y \)[/tex] approaches 1.
The limit then becomes:
[tex]\[ \lim_{y \to 1} \frac{y^2 + 5y - 6}{y - 1} \][/tex]
2. Simplify the numerator:
Factor the quadratic expression in the numerator [tex]\( y^2 + 5y - 6 \)[/tex]:
[tex]\[ y^2 + 5y - 6 = (y + 6)(y - 1) \][/tex]
This allows us to rewrite the limit as:
[tex]\[ \lim_{y \to 1} \frac{(y + 6)(y - 1)}{y - 1} \][/tex]
3. Cancel the common factor:
Notice that [tex]\( y - 1 \)[/tex] appears in both the numerator and the denominator, so we can cancel it out:
[tex]\[ \lim_{y \to 1} \frac{(y + 6)\cancel{(y - 1)}}{\cancel{(y - 1)}} = \lim_{y \to 1} (y + 6) \][/tex]
4. Evaluate the limit:
As [tex]\( y \)[/tex] approaches 1, we simply substitute [tex]\( y \)[/tex] with 1 in the remaining expression:
[tex]\[ (y + 6) \bigg|_{y = 1} = 1 + 6 = 7 \][/tex]
Therefore, the value of the limit is:
[tex]\[ \lim_{x \to \pi/2} \frac{\sin^2 x + 5 \sin x - 6}{\sin x - 1} = 7 \][/tex]
Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Westonci.ca is committed to providing accurate answers. Come back soon for more trustworthy information.